Race for the dragon heartstone - Halbrook, Kristin (Halbrook, Kristin. Silver Batal, 2020)
Silver Batal and her beloved water dragon Hiyyan continue their adventures across the sea and skies! Silver Batal and her best friend, Hiyyan, have narrowly escaped the greedy clutches of Queen Imea. With the queen's trackers hot on their tails, Silver and Hiyyan head into an exciting frozen world filled with ferocious ice dragons, new friends, and new foes. But when Hiyyan suffers a poisonous bite from a deadly dragon, Silver must find a legendary dragon heartstone to heal him. Their search leads to the mysterious Keep, the home of the reclusive and mysterious Watchers, where nothing is quite as it appears ... Perfect for fans of Roshani Chokshi and Sayantani DasGupta, this thrilling follow-up to Silver Batal and the Water Dragon Races will capture your heart.